Air change rates and aerosol dispersion in a room with ceiling and stand fans using computational fluid dynamics - Fernandez, Ken Bryan A. (Philippine Engineering Journal, 2023)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/9138/8069